Diaspora and globalization: a potential threat to the Malaysian security - Othman, Zaheruddin (Medwell Journal, 2013)
The world conflict caused diaspora but diaspora has also triggered conflicts.The movement of diaspora is no more conservative where it used to be from developing countries to developed countries, now diaspora is moving towards developing countries.As a result of that the effect of diaspora is no more focused on developed countries alone but developing countries are also exposed to diaspora activities. One of the major effects from the movement of diaspora is a threat to the national security.A close analysis was done using data from secondary cases of diaspora movement in a few countries.Research result shows that evolution of globalization gives effects to the movement trends and diaspora activities and Malaysia has the environment to allow diaspora to operate actively.